2014
DOI: 10.1002/ardp.201400271
|View full text |Cite
|
Sign up to set email alerts
|

A New Series of Antibacterial Nitrosopyrimidines: Synthesis and Structure–Activity Relationship

Abstract: New nitrosopyrimidines were synthesized and evaluated as potential antibacterial agents. Different compounds structurally related with 4,6-bis(alkyl or arylamino)-5-nitrosopyrimidines were evaluated. Some of these nitrosopyrimidines displayed significant antibacterial activity against human pathogenic bacteria. Among them compounds 1c, 2a-c, and 9a-c exhibited remarkable activity against methicillin-sensitive and -resistant Staphylococcus aureus, Escherichia coli, Yersinia enterocolitica, and Salmonella enteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Intramolecular hydrogen bonds (IMHBs) affect molecular properties significantly; for example, molecules become more lipophilic and may exhibit enhanced membrane permeability upon the formation of IMHBs . Molecules containing pseudo-ring formed by an IMHB have been proposed as bio-isosteres of several biologically important molecules and it has been proven that six-membered hydrogen bonded pseudo-rings effectively mimic an aromatic ring. Exceptionally stable IMHBs have recently been observed in polysubstituted 5-nitrosopyrimidine derivatives. When two hydrogen bond donors were in the neighboring positions to the nitroso group, two stable rotamers of the nitroso group were observed and even separated in several cases . The extraordinary stability of hydrogen bonds in these systems has been explained in terms of resonance-assisted hydrogen bonding (RAHB) and intramolecular charge transfer (push–pull interactions) …”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular hydrogen bonds (IMHBs) affect molecular properties significantly; for example, molecules become more lipophilic and may exhibit enhanced membrane permeability upon the formation of IMHBs . Molecules containing pseudo-ring formed by an IMHB have been proposed as bio-isosteres of several biologically important molecules and it has been proven that six-membered hydrogen bonded pseudo-rings effectively mimic an aromatic ring. Exceptionally stable IMHBs have recently been observed in polysubstituted 5-nitrosopyrimidine derivatives. When two hydrogen bond donors were in the neighboring positions to the nitroso group, two stable rotamers of the nitroso group were observed and even separated in several cases . The extraordinary stability of hydrogen bonds in these systems has been explained in terms of resonance-assisted hydrogen bonding (RAHB) and intramolecular charge transfer (push–pull interactions) …”
Section: Introductionmentioning
confidence: 99%
“…The NMR spectra for structure determination were recorded at room temperature on a spectrometer operating at 850.3 MHz for 1 H and 213.8 MHz for 13 C, or at 500.0 MHz for 1 H and 125.7 MHz for 13 C, or at 401.0 MHz for 1 H and 100.8 MHz for 13 C in DMSO-d 6 solutions (referenced to the solvent signal δ = 2.50 and 39.70 ppm, respectively). 1D and 2D correlation NMR experiments (COSY, HSQC, HMBC) were combined for the signal assignment.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Nitrosoarenes found many applications in synthetic organic chemistry. They, for example, play an important role as reactive metabolites, and are used as spin traps. , Recent studies of 5-nitrosopyrimidines revealed that the nitroso group can form unusually stable intramolecular hydrogen bonds (IMHBs) with amino substituents in neighboring C4 and C6 positions. In compounds with two different amino substituents in these positions, two rotamers of the nitroso group stabilized by the IMHBs were observed by NMR spectroscopy. The ratio of such conformers depends significantly on the substitution of the hydrogen bond donors, and the barriers of the rotamer interconversion were determined to be unusually high (>22 kcal/mol). In several cases, slow rotamer interconversion allowed the separation of pure rotamers by chromatographic techniques at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrosopyrimidines are an important group of heterocyclic compounds because of their value as excellent building blocks for the synthesis of novel compounds having interesting biological activities, including antibacterial (Olivella et al, 2015), antifungal (Olivella et al, 2012), anti-HIV (Al-Masoudi et al, 2016) and antiproliferative activity (Illá n-Cabeza et al, 2013), as well as enzyme inhibition, e.g. O 6 -alkylguanine-DNA alkyltransferase (AGT) inhibition (Roy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%